Old drugs: new complications. (22nd January 2013) - Batra, Sandeep; Wadhwa, Jyoti; Vaid, Ashok K; Sharma, Neelam
Abstract : This is a case of acute splenic and bilateral renal infarction in a patient with non-small cell lung carcinoma during chemotherapy with gemcitabine and cisplatin. Till date, bilateral renal infarction following gemcitabine and cisplatin has been reported only once in the past. The case that is being reported has had acute splenic and bilateral renal infarct and has not been reported previously. Splenic and renal infarction should be considered in the differential diagnosis of excruciating abdominal pain and backache in a patient on gemcitabine-based and cisplatin-based chemotherapy.